Investigasi Struktur Makro Material Nikel Sambungan Battery Pack Hasil Spot Welding - Nasrullah, Baso; Arsyad Suyuti, Muhammad; Nathaniel Sahusilawane, Allen; Rais Rahim, Muh; Akhmad Maulid Hadiullah (Politeknik Negeri Ujung Pandang, 2026)
Spot welding is one of the resistance welding methods widely applied in battery pack assembly due to its time efficiency and ease of implementation. This study aims to investigate the macrostructure of spot-welded nickel strip joints as connectors for battery cells and to optimize the process parameters using the Taguchi method. The varied parameters include welding mode, number of spots, and number of pulses. The welding process was carried out using an automatic spot welding machine, and the joints were analyzed through macrostructural observations using a digital microscope as well as shear strength testing. The results revealed that variations in welding parameters significantly affect nugget size. Based on Taguchi analysis, the optimal parameter combination produced a solid and symmetrical nugget, which correlated with higher shear strength of the joint. This study demonstrates that macrostructure has a strong correlation with joint strength and can serve as a reference in quality control of spot-welded battery pack joints.